Antioxidative Responses of Two Marine Microalgae During Acclimation to Static and Fluctuating Natural UV Radiation - Janknegt, Paul J. (2009)
Photoacclimation properties were investigated in two marine microalgae exposed to four ambient irradiance conditions: static photosynthetically active radiation (PAR: 400–700 nm), static PAR + UVR (280–700 nm), dynamic PAR and dynamic PAR + UVR. High light acclimated cultures of Thalassiosira weissflogii and Dunaliella tertiolecta were exposed outdoors for a maximum of 7 days. Dynamic irradiance was established by computer controlled vertical movement of 2 L bottles in a water filled basin. Immediate (<24 h), short‐term (1–3 days) and long‐term (4–7 days) photoacclimation was followed for antioxidants (superoxide dismutase, ascorbate peroxidase and glutathione cycling), growth and pigment pools. Changes in UVR sensitivity during photoacclimation were monitored by measuring UVR‐induced inhibition of carbon assimilation under standardized UV conditions using an indoor solar simulator. Both species showed immediate antioxidant responses due to their transfer to the outdoor conditions. Furthermore, upon outdoor exposure, carbon assimilation and growth rates were reduced in both species compared with initial conditions; however, these effects were most pronounced in D. tertiolecta. Outdoor UV exposure did not alter antioxidant levels when compared with PAR‐only controls in both species. In contrast, growth was significantly affected in the static UVR cultures, concurrent with significantly enhanced UVR resistance. We conclude that antioxidants play a minor role in the reinforcement of natural UVR resistance in T. weissflogii and D. tertiolecta.